Precursor B-Cell Acute Lymphoblastic Leukemia With MYC and BCL2 Rearrangements Presenting as Extensive Extranodal Disease in an Adolescent. Issue 4 (May 2021) - Oberoi, Sapna; Dawson, Angie; Marko, Daniel; Almiski, Muhamad; Higgins, Rick; Israels, Sara J.
Abstract : Combined rearrangements of MYC and BCL2 are rare in precursor B-cell acute lymphoblastic leukemia (B-ALL). A 14-year-old boy presented with swelling of the knee and face. Imaging revealed diffuse infiltration of lacrimal glands, parotid glands along with the extensive epidural disease. Morphology and immunophenotype of knee joint aspirate were consistent with precursor B-ALL. Fluorescent in situ hybridization identified rearrangements of MYC and BCL2 genes. The disease was refractory to intensive treatment. The patient died of progressive disease. Precursor B-ALL with combined MYC and BCL2 rearrangements is rare, characterized by an aggressive clinical course, and has an inadequate response to standard therapeutic approaches.